Daily science: Contributing to the popularization and diffusion of science - de Paula, Everton Luiz; de Oliveira Brasil Costa, Ricardo; Cordeiro Rocha , Luiz Henrique; Moreira dos Santos Gonçalves, Flavia Cesar (Guará Journal, 2022)
This article presents the results of an outreach project entitled "Everyday Science: Scientific Knowledge Through Radio Waves." Conducted in partnership with the University Radio, the project aims to disseminate scientific topics, particularly in the fields of Biological Sciences, Physics, Mathematics, and Chemistry. The radio program consists of a dialogue in which, based on everyday classroom situations, a teacher explains and discusses various concepts of the Natural and Exact Sciences with his students. The main objective is to spark interest in the Natural and Exact Sciences, as they are ever-present in people’s daily lives. In addition to radio broadcasts, the project also makes audio of the programs available via podcasts on a mobile phone app: the idea is that listeners with internet access can listen to programs of interest anytime, anywhere. Furthermore, to collaborate with high school teachers and students, CDs containing audio recordings of the programs were produced and sent to radio stations and schools within the scope of the Regional Education Superintendence of the municipality of the UNIVERSIDADE AUTORA. The aim is to contribute to the popularization of science and to produce supporting materials for use in high school classes in these subjects.